Targeted Training for Subspecialist Care in Children With Medical Complexity - Eibensteiner, Fabian; Ritschl, Valentin; Valent, Isabella; Schaup, Rebecca Michaela; Hellmann, Axana; Kaltenegger, Lukas; Daniel-Fischer, Lisa; Oviedo Flores, Krystell; Brandstaetter, Stefan; Stamm, Tanja; Schaden, Eva; Aufricht, Christoph; et al. (Frontiers in Pediatrics, 2022)
Background: Children with medical complexity (CMC) are prone to medical errors and longer hospital stays, while residents do not feel prepared to provide adequate medical care for this vulnerable population. No educational guidance for the training of future pediatric tertiary care specialists outside their field of expertise involving the multidisciplinary care of CMC exists. We investigated pediatric residents past educational needs and challenges to identify key learning content for future training involving care for CMC. Methods: This was a prospective mixed-methods study at a single pediatric tertiary care center. Qualitative semi-structured interviews with residents were conducted, submitted to thematic content analysis, linked to the American Board of Pediatrics (ABP) general pediatrics content outline, and analyzed with Importance Performance Analysis (IPA). Quantitative validation was focused on key themes of pediatric nephrology within the scope of an online survey among pediatric residents and specialists. Results: 16 interviews, median duration 69 minutes (IQR 35), were conducted. The 280 listed themes of the ABP general pediatrics content outline were reduced to 165 themes, with 86% (theoretical) knowledge, 12% practical skills, and 2% soft skills. IPA identified 23 knowledge themes to be of high importance where improvement is necessary and deemed fruitful. Quantitative validation among 84 residents and specialists (response rate 55%) of key themes in nephrology yielded high agreement among specialists in pediatric nephrology but low interrater agreement among trainees and “trained” non-nephrologists. The occurrence of themes in the qualitative interviews and their calculated importance in the quantitative survey were highly correlated (tau=0.57, p=0.001). Two clusters of high importance for other pediatric specialties emerged together with a contextual cluster of frequent encounters in both in- and outpatient care. Conclusion: Regarding patient safety, this study revealed the heterogenous aspects and the importance of training future pediatric tertiary care specialists outside their field of expertise involving the multidisciplinary care of CMC. Our results may lay the groundwork for future detailed analysis and development of training boot camps that might be able to aid the improvement of patient safety by decreasing preventable harm by medical errors, especially for vulnerable patient-groups, such as CMC in tertiary care pediatrics.